Contribution of Janata Awash Grant for Poverty Reduction in Makwanpur, Nepal - Timsina, Tirtha Raj; khatri, Bishnu Bahadur; Rijal, Nirajan; Shrestha, Binita (Historical Journal, 2024)
This research paper deals with the Janata Awash Grant, a program resembling Universal Basic Income (UBI), implemented in Raksirang Rural Municipality of Makawanpur District in Nepal, which specifically focuses on poverty reduction, social justice, and inclusion for impoverished families. The main aim of this paper is to examine the effectiveness of the Janata Awash Grant (JAG) in reducing poverty and promoting social justice among the designated families. The research uses a mixed-method approach, employing an explanatory sequential research design, and utilizes both primary and secondary data sources. Forty households out of 200 grant recipients were randomly chosen for primary data collection. Additionally, key informant interviews were conducted with selected representatives and informed beneficiaries to gather qualitative insights. The results indicate significant improvements in the economic status of recipient families, leading to a decrease in poverty rates and an overall enhancement in quality of life. Qualitative analysis highlights the broader societal and ethical impacts of receiving a guaranteed income, emphasizing the transformative potential of UBI beyond its monetary benefits.